2015
DOI: 10.1371/journal.pone.0143107
|View full text |Cite
|
Sign up to set email alerts
|

Negative Feedbacks by Isoprenoids on a Mevalonate Kinase Expressed in the Corpora Allata of Mosquitoes

Abstract: BackgroundJuvenile hormones (JH) regulate development and reproductive maturation in insects. JHs are synthesized through the mevalonate pathway (MVAP), an ancient metabolic pathway present in the three domains of life. Mevalonate kinase (MVK) is a key enzyme in the MVAP. MVK catalyzes the synthesis of phosphomevalonate (PM) by transferring the γ-phosphoryl group from ATP to the C5 hydroxyl oxygen of mevalonic acid (MA). Despite the importance of MVKs, these enzymes have been poorly characterized in insects.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…OeMVK 3D model showed similar fashion in other MVK proteins ( Fig. 2a) [2,3]. A conserved glycine-rich sequence "GSGLGSSA" which forms a phosphate-binding loop in all GHMP kinases, a conserved amino acid sequence "KLTGAGGGGC" that stabilizes the phosphate binding loop and a conserved motif contains "KIILAGEHA" PTS2 motif which is consisted of a part of the active site at similar positions as in Arabidopsis thaliana Mevalonate Kinase (NM_180753 ) and other plant MVK proteins [3].…”
Section: Characterization Of Oemvk Proteinsupporting
confidence: 65%
“…OeMVK 3D model showed similar fashion in other MVK proteins ( Fig. 2a) [2,3]. A conserved glycine-rich sequence "GSGLGSSA" which forms a phosphate-binding loop in all GHMP kinases, a conserved amino acid sequence "KLTGAGGGGC" that stabilizes the phosphate binding loop and a conserved motif contains "KIILAGEHA" PTS2 motif which is consisted of a part of the active site at similar positions as in Arabidopsis thaliana Mevalonate Kinase (NM_180753 ) and other plant MVK proteins [3].…”
Section: Characterization Of Oemvk Proteinsupporting
confidence: 65%
“…In A. aegypti , FPPase efficiently hydrolyzed FPP into farnesol, and silencing of AaFPPase-1 caused a significant decrease in JH biosynthesis, which strengthened the possibility that FPP acted as the crucial enzyme in regulating JH synthesis 22 . Similarly, the activity of A. aegypti Mk exhibited efficient feedback inhibition from long-chain isoprenoids, such as geranyl diphosphate and farnesyl diphosphate 61 . This study also showed that knockdown of Fpps 4 caused a significant decline in JH titer, leading to the darkening of cuticle and the molting disturbance in larvae (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…These results suggest that GDP might act as a physiological inhibitor in the synthesis of isoprenoids in the Corpora Allata of mosquitoes. In addition, research findings indicated that changing MVK activity can alter the flux of precursors and therefore regulate juvenile hormone biosynthesis (Nyati, Rivera‐Perez, & Noriega, ). Data presented in Table include diterpenoids with promising antiviral effects, including andrographolide, among others.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their lesser side effects and cost, therapies such as natural products, have attracted the attention of the scientific and medical communities as options to treat and manage DENV infections. Terpenes, a large and diverse class of Test system(s) Activity (possible mechanism(s)) References (Nyati, Rivera-Perez, & Noriega, 2015). Data presented in Table 1 include diterpenoids with promising antiviral effects, including andrographolide, among others.…”
Section: Discussionmentioning
confidence: 99%